Legal Aspects of the Functioning of the State Civil Service. / Aspectos jurídicos del funcionamiento del servicio público estatal - Prokofiev, Stanislav E.; Krasyukova, Natalia L.; Bogatyrev, Evgeny D.; Belyaev, Alexander M.; Eremin, Sergey G. (Utopía y Praxis Latinoamericana)
ABSTRACT In this work, various methods are used to reveal the topic: a systematic approach to the analysis of research on the organization and implementation of the public civil service, as well as the method of using logic, as in the presentation of all the material of the work, the relevant conclusions are formulated. The primary task of passing of the public civil service in the Russian Federation is signing of the service contract about the form of conducting a certain type of public service, and also establishment of the order and the reasons of dismissal from the public civil service. RESUMEN En este trabajo se utilizan diversos métodos para formular el tema: un enfoque sistemático en el análisis de la investigación sobre la organización y ejecución de la función pública, así como el uso del método lógico en la presentación de todo el material de traajo, se formulan las conclusiones pertinentes. La tarea principal de la transición del servicio público en la Federación de Rusia es la firma del contrato de servicios sobre la forma de realizar un determinado tipo de Servicio público, así como el establecimiento de la orden y las razones de despido del servicio público.